Ocular Manifestations in Thyroid Disorders in Karachi (Medical Forum Monthly, 2020)
Objective: To analyze the ocular findings in thyroid disorders presented in Karachi.Study Design: A Cross-sectional studyPlace and Duration of Study: This study was conducted at the outpatients departments of two tertiary care hospitals of Karachi, Liaquat National Hospital and Dow University of Health Sciences Ojha Campus, Karachi in the department of Endocrinology and Ophthalmology from June, 2018 to June, 2019.Materials and Methods: Inclusion criteria of thyroid disorder patients were; age between 12-60 years, known hypothyroidism or hyperthyroidism, finding of thyroid abnormalities and visible goiter or exophthalmos. The exclusion criteria were, known diabetic or hypertensive, on iodine containing drugs, pulsatile exophthalmos, poly glandular autoimmune diseases and lens/corneal/retinal abnormalities. One hundred and eleven patients were selected according to the inclusion criteria. After consent recent detailed history, clinical examination and ophthalmic examinations were done. Required laboratory and radiological investigations were done and analyzed. The data were entered in SPSS version 20 for descriptive and other relevant statistical analysis. Each patient was examined with slit lamp for anterior segment, snellen chart for measurement of visual acuity, ophthalmoscope for fundoscopy, Goldmann Applanation Tonometer for intraocular pressure measurement, Torch for examination of pupil and extraocular movements and Hertel exophthalmometer to measure amount of exophthalmos. CT and (Hertel) MRI in selected cases were done.Results: The mean age of involvement was 39+/- 15 years and there was female preponderance 2.6:1. Out of 111 patients 70% were hyperthyroid and 30% were fixed with the diagnosis of hypothyroidism. Almost 20% had bilateral proptosis while unilateral exophthalmos was 5.5%. Goiter was visible among 28%. Around 20% had family history of thyroid disorders and habitual usage of iodized salt was 17%. Addiction to smoking was 26%. The main ocular sign in hyperthyroidism was ocular pressure and increased myopia and while xerosis of eyes and loss of hairs in eyebrows were main ocular presentation among hypothyroidism. The most elicited sign in hyperthyroidism was lid lagging and eye protrusion while congested eye lids, dry eyes and weak ocular movements were main signs among hypothyroidism. Marcus Gunn pupil and papilledema were present in 2 patients. Optic neuropathy was present in one patient. The latter signs were red flag signs of oculopathies in hyperthyroidism.Conclusion: Eyes are good representative of thyroid disorders if examined according to the standard protocol. Hyperthyroidism has sine qua non ocular markers while in hypothyroidism the slow basal metabolic rate represents in eyes as xerosis and loss of eyebrows.